Free energies of undercooled phases - Ramachandrarao P.; Dubey K.S.; Lele S. (My University, 2025)
A novel approach for the estimation of the free energies of metastable liquid and allotropie phases has been presented. The method is based on the Taylor series expansion of the free energy différence between stable and metastable phases. The procedure has been applied to arrive at allotropie transformation temperatures in iron and also the isentropic temperature for any two coexisting phases. Results obtained strongly validate the expressions derived which involve only the use of equilibrium heat capacity and entropy data. © 1989.